Identification of food sources in tropical seagrass bed food web using triple stable isotopes and fatty acid signatures - Cui, Lijun; Jiang, Zhijian; Huang, Xiaoping; Liu, Songlin; Wu, Yunchao (Frontiers in Marine Science, 2023)
Identifying the trophic role of primary producers is the basis of assessing seagrass bed functions but remains difficult due to the underdetermined analysis method. Here, we analyzed the multiple isotopes (δ 13 C, δ 15 N, and δ 34 S values) and Fatty acid markers of food sources and macrobenthos in a tropical seagrass bed in summer and winter，and tried to combine these indicators to resolve the limitation of δ 13 C and δ 15 N values analysis. We found that the δ 13 C and δ 15 N values of epiphytes were like that of seagrass and macroalgae, while the δ 34 S values of epiphytes and macroalgae were significantly different, and the dominant unsaturated Fatty acid markers of seagrass (18:2n6c and 18:3n3) and epiphytes (16:1n7) were obviously different. Therefore, the combination of multiple isotopes and Fatty acid markers can effectively distinguish the complex food source. In addition, we also found that multiple isotopes were more suitable to identify the food sources of polychaetes and snails with simple diets, fatty acids were more suitable to identify the food sources of crustaceans with complex diets, but their combination is essential in identifying the diets of macrobenthos since the wide range of isotopic values for omnivores crustaceans and the Fatty acid markers transformation during snails and polychaetes assimilation might mislead us when only isotopes or Fatty acid markers were used.